Analysis of Teacher Perceptions: Efforts to Grow Science Process Skills in Elementary Schools through Learning Media - Ningsih, Mariza Putri Sari Dewi; Nadiroh, Nadiroh; Usman, Herlina (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Learning science is very closely related to the environment of students, but the benefits are still not felt by students.Â The purpose of this study was to know teacher perceptions in fostering science process skills of elementary school students through learning media. Needs analysis in terms of the teacher’s point of view to see the extent to which science process skills have been pursued, then expected can assist teachers in knowing the needs that are by the characteristics of the student learning environment in fostering science process skills. The method in this research is qualitative research with data collection techniques carried out through interviews and questionnaire. The subjects of the study were 9 elementary school teachers who taught science and used learning media. The results showed that teachers now have a good understanding of science process skills. However, teachers have difficulty in designing the learning process and implementation because there is no available learning media that can be used to support SPS learning. Therefore, the need for a digital web learning media according to the characteristics of elementary school that can be used to encourage SPS.